ADHD From Etiology to Comorbidity - Gregorič Kumperščak, Hojka (IntechOpen, 2021)
Attention Deficit Hyperactivity Disorder (ADHD) is the most prevalent neurodevelopmental disorder. Previously, it was considered a disorder that affected children only. Recently, however, there is no doubt that ADHD can affect adults as well, but with different clinical presentation. Thus, it is critical to understand how the clinical picture of the disorder changes with development. Traditional ADHD diagnostic procedures are broadening and incorporating new entities like endophenotypes. Comorbidity is a rule, especially if ADHD is not recognized and treated early. New genetic studies bring deeper and more concise knowledge about the disorder's etiology. This book addresses these aspects of ADHD to bring about more clarity and understanding of the disorder.